2017
DOI: 10.1103/physreve.96.032214
|View full text |Cite
|
Sign up to set email alerts
|

Unifying perspective: Solitary traveling waves as discrete breathers in Hamiltonian lattices and energy criteria for their stability

Abstract: In this work, we provide two complementary perspectives for the (spectral) stability of solitary traveling waves in Hamiltonian nonlinear dynamical lattices, of which the Fermi-Pasta-Ulam and the Toda lattice are prototypical examples. One is as an eigenvalue problem for a stationary solution in a cotraveling frame, while the other is as a periodic orbit modulo shifts. We connect the eigenvalues of the former with the Floquet multipliers of the latter and using this formulation derive an energy-based spectral … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 33 publications
2
38
0
Order By: Relevance
“…Thirdly, this criterion is similar in spirit with the criteria that we have established in our recent works in [21,22] (and with the classic work of [34]). We have, in fact, attempted to extract such a "theorem" following the pattern of the corresponding proofs in [34,21,22]. However, this attempt encounters two significant stumbling blocks.…”
Section: Conclusion Discussion and Future Workmentioning
confidence: 58%
See 2 more Smart Citations
“…Thirdly, this criterion is similar in spirit with the criteria that we have established in our recent works in [21,22] (and with the classic work of [34]). We have, in fact, attempted to extract such a "theorem" following the pattern of the corresponding proofs in [34,21,22]. However, this attempt encounters two significant stumbling blocks.…”
Section: Conclusion Discussion and Future Workmentioning
confidence: 58%
“…This, in turn, allowed a definitive computation of the Floquet multipliers associated with the solution considered as a periodic orbit (modulo shifts). We have argued both here and in our earlier works [21,22] that this is a beneficial way of examining traveling wave solutions on a lattice as it helps to understand their stability and hence provides an informed view on their dynamics.…”
Section: Conclusion Discussion and Future Workmentioning
confidence: 87%
See 1 more Smart Citation
“…More specifically, we showed that when H ′ (c 0 ) = 0 for some critical velocity c 0 , a pair of eigenvalues associated with the traveling wave (in the co-traveling frame of reference in which the wave is steady) cross zero and emerge on the real axis when c is either above or below c 0 , thus creating instability. While this energy-based criterion first appeared in [16], where it was motivated by the study of the FPU problem in the near-sonic limit, in [31] we provided a concise proof as well as an explicit leading-order calculation for these two near-zero eigenvalues. In addition, we tested the criterion numerically for a range of lattice problems.…”
Section: Introductionmentioning
confidence: 93%
“…In a recent paper [31], inspired by and extending the fundamental work of [16], we examined the sufficient (but not necessary) condition for a change in the wave's spectral stability occurring when the function H(c) changes its monotonicity. More specifically, we showed that when H ′ (c 0 ) = 0 for some critical velocity c 0 , a pair of eigenvalues associated with the traveling wave (in the co-traveling frame of reference in which the wave is steady) cross zero and emerge on the real axis when c is either above or below c 0 , thus creating instability.…”
Section: Introductionmentioning
confidence: 99%